SAMPLES OF THE WISDOM OF IMAM ABU HAMID GHAZALI QUOTED IN THE GREAT WORKS - Ochilov Yakub Saydulloyevich (Scholar Express Journal, 2023)
This article presents examples of wisdom found in the works of Abu Hamid al-Ghazali, which include knowledge, economy, commerce, livelihood, piety, justice of leaders, knowledge of scientists, generosity of the rich, prayer of the needy, lying, suspicion and detailed information about the situations in the heart and the beautiful virtues and feelings of humanity in the heart
Keywords: heart; arrogance; justice; theft